Design and develop a prototype for microsoft imagine cup 2024 (A) - Ng, Yu Wen (Nanyang Technological University, 2024)
Art therapy is a form of psychotherapy using visual art materials. It is a psychotherapeutic approach which makes use of creative process to enhance the well-being of the individual. The individual can express themselves through creative techniques such as drawing, painting, and sculpting. Art therapy sessions are held either weekly or biweekly, thus more sessions may need to be held for art therapist to understand their clients better.